"Mirror agnosia" in a patient with right occipitotemporal infarct - Menon Bijoy; Shanbhogue K; Mutharasu C; Gopinathan S; Balasubramanian S; Chandramohan; Kingsly Jebasingh; Jawahar M (Annals of Indian Academy of Neurology, 2006)
We report the clinical profile and investigation of K, a patient suffering from agnosia for the concept of "mirrors". Normal people rarely confuse a mirror image for the real image. Our patient ′K′ has intact attention, memory and language with a left visual neglect with left hemianopia. When shown an object on his left with a mirror kept sagitally on his right, K grabs for the reflection and even gropes behind the mirror for it. Yet, when shown the mirror alone, he is able to tell that it is a mirror. Thus the concept of a ′mirror′ is lost in the experimental paradigm. An explanation for mirror ′agnosia′ is provided and recent controversies in the analysis of visuospatial functions in humans is highlighted.